Web Services Design and Implementation through C# .NET - Abd Khalil Fdheel, Mais; Kadhum Abboud, Izz; Saleh Hassan, Abbas (Journal of Engineering and Sustainable Development, 2014)
The purpose of this paper is to give a practical introduction to web services and describe their increased importance in information technology world, also Explain everything about Web Services in .Net, web services benefits, explain what web service mean and how it differ from websites technology, also give practical examples to illustrate how to design and implement web services using .NET and C#, and how to lead auser to reach and consume (use) web service in network distributed systems and internet.